GAME AS AN ELEMENT OF HYGIENE MOTIVATION OF PRE-SCHOOLERS - V.S. Melnyk; L.F. Horzov (Український стоматологічний альманах)
The aim of our research was to evaluate the effectiveness of a game in teaching the pre-schoolers, and the degree of learning to preserve children`s dental health.